Karapan Sapi (Cow Race) Cultures in Madura: Economics Values and Owners' Prestige - Agnes Sintia Debby; Achdiar Redy Setiawan (International Journal of Religious and Cultural Studies, 2023)
The study aims to unravel the values underlying the culture of the cow race (karapan sapi) in the Madurese community. This research employed qualitative study using an ethnographic approach. The study found that in the planning stage, the cow race is a reflection of economic value, especially during the cows’ productive life period. Second, in the implementation phase, the cow races are a reflection of the prestige of the cow owner. Cow owners who take part and win the race feel that their status is higher since Madurese believes that people who have cows are often materially abundant. Third, in the recording phase, the cost of the cow race is based on "trust". The novelty of this research lies on the economic values and owners’ prestige as research findings in the culture of Karapan Sapi.